2021
DOI: 10.3390/ijerph18094580
|View full text |Cite
|
Sign up to set email alerts
|

A Drone Logistic Model for Transporting the Complete Analytic Volume of a Large-Scale University Laboratory

Abstract: We present a model for drone transport of the complete annual analytic volume of 6.5 million analyses— (routine and emergency) between two inner-city university laboratories at Oslo University Hospital located 1.8 km apart and with a time restriction for the analyses of no more than 60 min. The total laboratory activity was analyzed per min for the complete year of 2018. The time from the clinical ordering of tests to the loading of the drone, drone transport time, and analysis time after the sample arrived at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Emerging technologies are usually influenced by the existing institutional solutions (in our context, hospitals), which operate in a stable configuration until a new technology emerges and creates an interplay of multiple technologies [37]. Compliance with legacy systems, as well as ethical standards and standards of clinical and laboratory processes, are crucial in such processes [44].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Emerging technologies are usually influenced by the existing institutional solutions (in our context, hospitals), which operate in a stable configuration until a new technology emerges and creates an interplay of multiple technologies [37]. Compliance with legacy systems, as well as ethical standards and standards of clinical and laboratory processes, are crucial in such processes [44].…”
Section: Figurementioning
confidence: 99%
“…Johannessen et al [44] concluded that it would require extensive research to understand how best to engage clinical and laboratory leaders and managers in actively facilitating long-term improvement processes to optimize drone transport solutions. They highlighted the relevance of well-known specialized methods that focus on looking for waste in production processes to improve workflows and create more value with less effort: the LEAN method (originating from the Toyota car manufacturing system) and Six Sigma (originating from Motorola).…”
Section: Facilitating Innovation Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both clinical procedure times and existing laboratory processes may be a function of transport mode. It should be expected that such internal processing times may influence the overall time perspective from acquiring biologic samples from the patient to final analysis [20].…”
Section: Limitationsmentioning
confidence: 99%
“…Regarding biologic transport, a previous study at Oslo University Hospital (OUS) found that drone transport could theoretically enable the merger of two of the largest laboratories, achieving potential annual savings of NOK 100 million (EUR 9.5 million) [20]. Although such radical solutions may be uncommon, promising reductions in cost duplications may be achieved if laboratories can be networked.…”
Section: Introductionmentioning
confidence: 99%